Cell behavior observation and gene expression analysis of melanoma associated with stromal fibroblasts in a three‐dimensional magnetic cell culture array. (21st November 2012) - Okochi, Mina; Matsumura, Taku; Yamamoto,; Shuhei; Nakayama, Eiichi; Jimbow, Kowichi; Honda, Hiroyuki
Abstract A three‐dimensional (3D) multicellular tumor spheroid culture array has been fabricated using a magnetic force‐based cell patterning method, analyzing the effect of stromal fibroblast on the invasive capacity of melanoma. Formation of spheroids was observed when array‐like multicellular patterns of melanoma were developed using a pin‐holder device made of magnetic soft iron and an external magnet, which enables the assembly of the magnetically labeled cells on the collagen gel‐coated surface as array‐like cell patterns. The interaction of fibroblast on the invasion of melanoma was investigated using three types of cell interaction models: (i) fibroblasts were magnetically labeled and patterned together in array with melanoma spheroids (direct‐interaction model), (ii) fibroblasts coexisting in the upper collagen gel (indirect‐interaction model) of melanoma spheroids, and (iii) fibroblast‐sheets coexisting under melanoma spheroids (fibroblast‐sheet model). The fibroblast‐sheet model has largely increased the invasive capacity of melanoma, and the promotion of adhesion, migration, and invasion were also observed. In the fibroblast‐sheet model, the expression of IL‐8 and MMP‐2 increased by 24‐fold and 2‐fold, respectively, in real time RT‐PCR compared to the absence of fibroblasts. The results presented in this study demonstrate the importance of fibroblast interaction to invasive capacity of melanoma in the 3D in vitro bioengineered tumor microenvironment. © 2012 American Institute of Chemical Engineers Biotechnol. Prog., 2013